A new genus and some new descriptions of the tribe Aemodogryllini (Orthoptera, Rhaphidophoridae, Aemodogryllinae; Aemodogryllini) from China - Qin, Yanyan; Liu, Xianwei; Li, Kai (Zootaxa, 2017)
In the present paper, a new genus Pseudotachycines gen. nov. and five new species are identified and described: Pseudotachycines deformis sp. nov., Pseudotachycines inermis sp. nov., Pseudotachycines yueyangensis sp. nov., Pseudotachycines volutus sp. nov., Pseudotachycines trapezialis sp. nov., Pseudotachycines ovalilobatus (Gorochov, 2010) comb. nov. a new combination is mentioned. A key to the species of Pseudotachycines gen. nov. is provided.